Research on recycling decision of waste power batteries under subsidy-penalty policy - Wenbin, Wang; Ye, Liu; Luosheng, Zhong; Jinyu, Qi; Peng, Quan (Scientific Insights and Discoveries Review, 2024)
By constructing an evolutionary Bowan model of the recycling decisions of power battery manufacturers (hereinafter referred to as battery manufacturers) and new energy vehicle manufacturers (hereinafter referred to as vehicle manufacturers) on waste power battery recycling, the factors affecting whether battery manufacturers and vehicle manufacturers choose to recycle or not, as well as the conditions under which both decide to recycle, are analyzed under two scenarios: no government intervention and implementation of a subsidy-penalty policy. The system dynamics model is then used for simulation. The results show that: (1) In the case of no government intervention, when the repurchase price of the battery manufacturer is greater than the maximum value of the sum of the unit recycling price and recycling cost of the battery manufacturer and vehicle manufacturer, both recycle waste power batteries. (2) In the case of the government implementing a subsidy-penalty policy, the repurchase price of the battery manufacturer is not affected by the government penalty. Compared with the case of no intervention, an increase in the government unit subsidy will reduce the minimum repurchase price of the battery manufacturer. (3) When the government implements a subsidy-penalty policy, when the unit subsidy is greater than the threshold, the battery manufacturer and vehicle manufacturer choose to recycle waste power batteries. (4) The government's implementation of a subsidy-penalty policy can significantly shorten the time it takes for battery manufacturers and vehicle manufacturers to recycle waste power batteries. This study can provide a reference for the government to promote battery manufacturers and new energy vehicle manufacturers to recycle used power batteries.